THE ROLE OF DEMOGRAPHIC FACTORS OF PAKISTANI WOMEN IN THE ENTREPRENEURIAL PERFORMANCE - Dr. Arooj Zeb; Dr. Samina Begum; Ms. Awoesha Rahat; Dr. Wahid Raza (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
The purpose of this study is to explore the demographic factors that influence the success of women entrepreneurs in Pakistan. The study aims to identify the impact of age and education level on the entrepreneurial performance of women entrepreneurs. The research instrument used in this study is a survey questionnaire that was distributed to a sample of 254 women entrepreneurs in Pakistan. The population of this study comprises women entrepreneurs who are running their own ventures in various sectors of the economy. Comparative analyses were done on the data. The results show that women entrepreneurs who are relatively younger in age are more motivated, initiative, and productive to achieve targets related to entrepreneurial matters. Moreover, the study found that educated women entrepreneurs are more likely to succeed and enjoy more success than uneducated ones. Based on the findings of this study, several recommendations are provided for policymakers, government agencies, and other stakeholders. Firstly, policymakers should focus on creating an enabling environment for women entrepreneurs by providing them with access to finance, training, and other necessary resources. Secondly, government agencies should develop programs and policies that specifically target women entrepreneurs and address the challenges they face in starting and running their own ventures. Thirdly, the education system should be reformed to provide women entrepreneurs with the necessary skills and knowledge to succeed in their ventures. Finally, further research is needed to explore other demographic factors that may influence the success of women entrepreneurs in Pakistan.